Associations of white matter hyperintensity with frailty, sarcopenia, and nutritional risk: an analysis of an acute ischemic stroke patient database - Akimoto, Takayoshi; Sugi, Chiharu; Tasaki, Kenta; Oshita, Natsuki; Natori, Naotoshi; Mizoguchi, Tomotaka; Ishihara, Masaki; Hara, Makoto; Nakajima, Hideto (Frontiers in Medicine, 2025)
IntroductionWhite matter hyperintensity (WMH), frailty, sarcopenia, and nutritional risk are prevalent and critical factors in geriatric care. This study aimed to investigate the associations between WMH and frailty, sarcopenia, and nutritional risk status using data derived from an acute ischemic stroke (AIS) hospitalization database.MethodsImages of brain magnetic resonance imaging were reviewed for patients aged ≥60 years who were hospitalized for AIS. WMH was classified into deep white matter hyperintensity (DWMH) and periventricular hyperintensity (PVH) and graded on a scale from 0 to 3 using the Fazekas scale. Frailty was assessed on the basis of the frailty screening index derived from the interview data. Sarcopenia was diagnosed based on grip strength measured on the nonparalyzed side and muscle mass assessed using bioelectrical impedance analysis. The nutritional risk status was evaluated using the Geriatric Nutritional Risk Index.ResultsDWMH of grade ≥1 was observed in 92% of patients and PVH in 94%. Trend tests for ordinal scales indicated that DWMH and PVH were associated with older age, a higher female proportion, greater stroke severity, longer hospital stay, and lower grip strength and muscle mass. DWMH alone was associated with a higher pneumonia incidence during hospitalization. PVH alone was significantly associated with an increased prevalence of frailty, sarcopenia, and nutritional risk status. To further explore these associations, logistic regression analyses were performed with grade ≥2 PVH, frailty, and sarcopenia as outcome variables. The analyses identified age, male sex, PVH, and sarcopenia as independent predictors of frailty; nutritional risk and frailty as predictors of sarcopenia; and frailty as the sole predictor of PVH.DiscussionWMH is highly prevalent among older adult patients with AIS, with PVH particularly associated with frailty, sarcopenia, and nutritional risk status. These conditions appear to be interrelated, and the findings suggest that sarcopenia and PVH can contribute to frailty development.